Development of a Flipbook-Based E-LKPD Using Bruner’s Cognitive Theory to Enhance Learning Independence of Third-Grade Elementary School Students - Sanseni Safitri; Darmansyah; Syafri Ahmad; Melva Zainil (Postgraduate, University of Mataram, 2026)
This study addresses the limited integration of cognitive learning theory with interactive digital media in elementary mathematics instruction, which contributes to low student learning independence. The study aims to develop and evaluate a flipbook-based electronic student worksheet (E-LKPD) grounded in Bruner’s cognitive theory. A Research and Development (R&D) approach was employed using the ADDIE model, involving third-grade students at SDN 25 Sungai Sirah Hilir (N = 50; experimental and control groups). Data were collected through expert validation sheets, practicality questionnaires, learning independence instruments, and pretest–posttest measures, and analyzed using descriptive statistics, N-Gain, and an independent sample t-test. The results indicate that the developed E-LKPD achieved very high validity (92.55%) and practicality (teacher: 98.40%; students: 97.00%). The effectiveness test showed that the experimental group outperformed the control group in learning independence (80.20% vs. 67.47%) with a significant difference (p < 0.05) and a higher N-Gain score (0.80 vs. 0.43). These findings demonstrate that integrating Bruner’s cognitive theory through enactive, iconic, and symbolic stages in flipbook-based E-LKPD enhances students’ learning independence. Therefore, the developed E-LKPD is feasible and effective as an innovative instructional medium to support independent learning in elementary mathematics.